Smartphone Authentication of Unclonable Anticounterfeiting Labels based on a Microlens Array atop a Microphosphor‐Doped Layer. Issue 6 (27th January 2023) - Kumar, Vinay; Gota, Fabrizio; Neyret, Julien; Katumo, Ngei; Chauhan, Aditya; Dottermusch, Stephan; Richards, Bryce S.; Howard, Ian A.
Abstract: A phosphor‐particle‐loaded microlens array on a polymer substrate offers an attractive unclonable anticounterfeiting label design. A random pattern of bright emission points is created due to the random coincidences of light focused by a microlens with an underlying phosphor microparticle. The change of the bright point patter with the angle of the incident light (owing to a shift in the locations of the focal points) makes the labels unclonable. This work examines the authentication of such labels using a single smartphone. The smartphone flashlight provides illumination whereas the camera is used for detection (optical filters prevent capture of scattered source light). A 196‐bit binary string is created from the captured images to identify which lenses in the 14 × 14 array create bright emission points for a given position of the smartphone. The classification of test and reference images as matching or not is achieved with >99% confidence, as is a 1 cm tolerance for the positioning accuracy of the smartphone. Moreover, authentication is possible for different distances between flash and camera provided this is less than 3 cm. In summary, the present work quantifies the good potential of the microlens array microphosphor unclonable label concept for authentication using a smartphone. Abstract : An unclonable label designed to be authenticated using a smartphone is presented. The label is made from a microlens array on top of a phosphor‐doped layer. A pattern of emission points is observed with the camera when the label is excited by the flashlight. This pattern change as the phone is moved making the labels highly resistant to cloning.